Implementasi Pendidikan Profetik dalam Membentuk Karakter Peserta Didik di Sekolah Dasar Al-Baitul Amien Jember Tahun Pelajaran 2019/2020 - Sinta Yulis Pratiwi; Lailatul Usriyah (HMPS PGMI FTIK IAIN Jember, 2020)
This research was conducted at Al-Baitul Amien Elementary School Jember which aims to answer the problem 1) How is the concept of prophetic education implementation in shaping the character of students at Al-Baitul Amien Elementary School Jember? 2) How is the implementation of prophetic education in shaping the character of students at Al-Baitul Amien Elementary School Jember? 3) How to evaluate the implementation of prophetic education in shaping the character of students at Al-Baitul Amien Elementary School Jember ? The method used in this study is a qualitative research method. The approach used is descriptive qualitative approach. The data collection techniques use interviews, observation, and documentation. And the validity of the data use triangulation of sources and techniques. The results obtained from this study indicate 1) The concept of prophetic education in shaping the character of students at Al-Baitul Amien Elementary School Jember in 2019/2020 school year in the form of the formation of a unique curriculum made based on the mosque's historical values, religious habituation programs and commemoration of Islamic holidays. 2) Implementation of prophetic education in shaping the character of students at Al-Baitul Amien Elementary School Jember 2019/2020 academic year in the form of some activities: Dhuha Prayers, Dhuhur and Ashar prayer Congregational, Habituation of reciting Asmaul Husna, Tahfidz Qur’an. 3) Evaluation obtained from the implementation of prophetic education, is the formation of students' character is influenced by internal factors, from within the students selves and external factors which include the environment and school activities.Keywords : implementation, prophetic education, character Penelitian ini dilakukan di Sekolah Dasar Al-Baitul Amien Jember yang bertujuan untuk menjawab permasalahan 1) Bagaimana konsep implementasi pendidikan profetik dalam membentuk karakter peserta didik di Sekolah Dasar Al-Baitul Amien Jember? 2) Bagaimana implementasi pendidikan profetik dalam membentuk karakter peserta didik di Sekolah Dasar Al-Baitul Amien Jember? 3) Bagaimana evaluasi implementasi pendidikan profetik dalam membentuk karakter peserta didik di Sekolah Dasar Al-Baitul Amien Jember?. Metode yang dipakai dalam penelitian ini adalah metode penelitian kualitatif. Pendekatan yang digunakan yaitu pendekatan kualitatif deskriptif. Adapun teknik pengumpulan data menggunakan wawancara, observasi, dan dokumentasi. Dan keabsahan datanya menggunakan triangulasi sumber dan teknik. Hasil yang diperoleh dari penelitian ini menunjukkan 1) Konsep pendidikan profetik dalam membentuk karakter peserta didik di Sekolah Dasar Al – Baitul Amien Jember tahun pelajaran 2019/2020 berupa pembentukan kurikulum khas yang dibuat berdasarkan nilai historis masjid, program pembiasaan keagamaan serta peringatan hari besar Islam. 2) Implementasi pendidikan profetik dalam membentuk karakter peserta didik di Sekolah Dasar Al – Baitul Amien Jember tahun pelajaran 2019/2020 berupa kegiatan: Sholat Dhuha, Sholat Dhuhur dan Ashar Berjamaah, Pembiasaan Asmaul Husna, Tahfidz Qur’an. 3) Evaluasi yang diperoleh dari pelaksanaan pendidikan profetik yakni, pembentukan karakter peserta didik dipengaruhi oleh faktor internal yakni dari dalam diri peserta didik dan faktor eksternal yakni meliputi lingkungan dan kegiatan sekolah. Kata Kunci : Implementasi, Pendidikan Profetik, Karakter